A Cross-sectional Survey of the North American Skull Base Society: Current Practice Patterns of Vestibular Schwannoma Evaluation and Management in North America - Carlson, Matthew L.; Van Gompel, Jamie J.; Wiet, R. Mark; Tombers, Nicole M.; Devaiah, Anand K.; Lal, Devyani; Morcos, Jacques J.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background Very few studies have examined vestibular schwannoma (VS) management trends across centers and between providers. The objective of this study is to examine current practice trends, variance in treatment philosophies, and nuanced or controversial aspects of VS care across North America.Methods This is a cross-sectional survey of North American Skull Base Society (NASBS) members who report regular involvement in VS care.Results A total of 57 completed surveys were returned. Most respondents claimed to have over 20 years of experience and the majority reported working in an academic practice with an affiliated otolaryngology and/or neurosurgery residency program. Sixty-three percent of respondents claimed to evaluate VS patients in clinic with both an otolaryngologist and neurosurgeon involved. Eighty-six percent of respondents claimed to operate on VS with both an otolaryngologist and neurosurgeon involved, while only 18% of neurosurgeons and 9% of otolaryngologists performed surgery alone. There was a wide range in the number of cases evaluated at each center annually. Similarly, there was wide variation in the number of patients treated with microsurgery and radiation at each center. Additional details regarding management preferences for microsurgery, stereotactic radiosurgery, stereotactic radiotherapy, and conservative observation are presented.Conclusion VS management practices vary between providers and centers. Overall, most centers employ a multidisciplinary approach to management with collaboration between otolaryngology and neurosurgery. Overall, survey responses concur with previous studies suggesting a shift toward conservatism in management.
Keywords: vestibular schwannoma; acoustic neuroma; skull base surgery; cranial fossa; microsurgery; radiosurgery